STRATEGI MEWUJUDKAN KEMANDIRIAN SEKTOR FINANSIAL LOKAL MELALUI SUSTAINABILITAS LEMBAGA KEUANGAN MIKRO SYARIAH (BAITUL MAAL WATAMWIL, BMT) - Indra, Yus (UNIVERSITAS PGRI MADIUN, 2018)
Abstract. Sustainability of Sharia Microfinance Institution or BMT is influenced by institutional sustainability, financial sustainability and external support. Aspects of sustainability are organizations, policies and procedures, internal control systems, tasks and authorities, financing risk management, human resources and outreach of products and activities, aspects affecting financial sustainability are capital adequacy, asset quality, liquidity , profitability and efficiency, while the factors affecting the external support are Laws and Regulations, Supervisory of authority and Associate Agencies (APEX). To build sustainability BMT then must attention to aspects mentioned above. This research is motivated by previous studies on financial sustainability of micro finance institutions, through best practice approach in financial institution generally conducted research to get, test and reconstruct to other aspects of sustainability of microfinance institution, that is aspect related to institution. This is due to the limited research that discusses institutional sustainability. Based on the research, it can be concluded that sustainability of BMT is influenced by institutional sustainability, financial sustainability and external support, but in the implementation stage it is necessary to re-implement the management based on best practice approach of bankingKeyword : sustainability, governance Abstrak. Sustainabilitas Lembaga Keuangan Mikro Syariah atau BMT dipengaruhi oleh sustainabilitas kelembagaan (institutional sustainability), sustainabilitas keuangan (financial sustainability) dan dukungan eksternal. Aspek yang mempengaruhi sustainabilitas adalah organisasi, kebijakan dan prosedur, sistem pengendalian internal, tugas dan kewenangan, manajemen risiko pembiayaan, Sumber Daya Insani dan keterjangkauan produk dan aktivitas. Aspek yang mempengaruhi sustainabilitas keuangan adalah kecukupan permodalan, kualitas aset, likuiditas, profitabilitas dan efisiensi, sedangkan faktor yang mempengaruhi dukungan eketernal adalah Undang-Undang dan regulasi, otoritas pembinaan dan pengawasan dan lembaga pengayom (APEX). Penelitian ini dilatarbelakangi oleh penelitian terdahulu mengenai sustainabilitas keuangan lembaga keuangan mikro, melalui pendekatan best practice perbankan dilakukan penelitian untuk merekontruksi kembali hasil penelitian terhadap aspek-aspek dari sustainabilitas lembaga keuangan mikro, yaitu aspek-aspek yang terkait dengan kelembagaan (institutional). Hal ini mengingat masih terbatasnya penelitian yang membahas mengenai sustainabilitas kelembagaan (institutional sustainability). Berdasarkan penelitian diperoleh hasil bahwa sustainabilitas BMT dipengaruhi oleh sustainabilitas kelembagaan (institutional sustainability), sustainabilitas keuangan (financial sustainability) dan dukungan eksternal, namun dalam tahap implementasinya perlu dilakukan pentatakelolaan kembali berdasarkan pendekatan best practice perbankan.Kata Kunci : sustainabilitas, tatakelola